2016
DOI: 10.1016/j.electacta.2016.04.164
|View full text |Cite
|
Sign up to set email alerts
|

Durable Membrane Electrode Assemblies for Proton Exchange Membrane Electrolyzer Systems Operating at High Current Densities

Abstract: High efficiencies, wide operation range and rapid response time have motivated the recent interest in proton exchange membrane (PEM) electrolysis for hydrogen generation with surplus electricity. However, degradation at high current densities and the associated mechanism has not been thoroughly explored so far. In this work, membrane electrode assemblies (MEA) from different suppliers are aged in a commercial PEM electrolyzer (2.5 N m 3 H 2 h -1 ), operating up to 4 A cm -2 for more than 750 h. In all cases, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
87
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(96 citation statements)
references
References 57 publications
5
87
1
3
Order By: Relevance
“…5a and b show a progressive increase in performance (decrease of E cell ) of these cells compared to the initial one. This phenomenon was previously observed for other stacks as well and the increase is mostly attributed to MEA aging effects46, which suddenly stop after the first 500 h (Figure S5a) in which the PEM electrolyzer unit was shut-down on purpose.…”
Section: Discussion Of Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…5a and b show a progressive increase in performance (decrease of E cell ) of these cells compared to the initial one. This phenomenon was previously observed for other stacks as well and the increase is mostly attributed to MEA aging effects46, which suddenly stop after the first 500 h (Figure S5a) in which the PEM electrolyzer unit was shut-down on purpose.…”
Section: Discussion Of Resultssupporting
confidence: 78%
“…If the tests would have been carried out at 2 A cm −2 , then a stack temperature of approx. 55–60 °C would be achieved46. Yet, we opted for a more conservative 1 A cm −2 due to the following.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Most of the literature is focused on the degradation phenomena related to the CCM. [88][89][90][91][92][93][94] Typical membrane degradation originates from thermal, chemical and mechanical stressors present during operation. 95 Polymer membranes, usually PFSA membranes, e.g.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] However, some research groups such as Rozain et al, 13,14 Lettenmeier et al 15 and Siracusano et al 5,16 among others have studied EIS of PEMECs in further detail, but most often at low current densities in the activation region of the iV-curve, where the oxygen evolution reaction (OER) current density is very low. [5][6][7][8]13,14,16,17 Only a few research groups have reported EIS measured at higher current densities in the linear region of the iV-curve during the OER.…”
mentioning
confidence: 99%